Isolation of myeloma variants with predefined variant surface immunoglobulin by cell sorting. - Liesegang, B (1978)
We describe a procedure for the isolation of somatic cell variants in which gene products are expressed on the cell surface that are not expressed in the wild type. Cloned cells of the myeloma line MPC 11, which expresses an IgG2b protein, were incubated with an antiserum specific for IgGI and IgG2a. Cells reacting with this antiserum were stained with a fluorescent anti-antiserum and enriched in three cycles of sorting in the fluorescence-activated cell sorter and subsequent growth in vitro. From the enriched population two variants were isolated by cloning in soft agar. One of them expressed a variant immunoglobulin that types serologically as an IgG2a but whose variable portion was idiotypically related to that of the MPC 11 wild-type protein.